Soy Pulp Extract Inhibits Angiotensin I-Converting Enzyme (ACE) Activity In Vitro: Evidence for Its Potential Hypertension-Improving Action. (4th May 2017) - Nishibori, Naoyoshi; Kishibuchi, Reina; Morita, Kyoji
ABSTRACT: Soy pulp, called "okara" in Japanese, is known as a by-product of the production of bean curd (tofu), and expected to contain a variety of biologically active substances derived from soybean. However, the biological activities of okara ingredients have not yet been fully understood, and the effectiveness of okara as a functional food seems necessary to be further evaluated. Then the effect of okara extract on angiotensin I-converting enzyme (ACE) activity was examined in vitro, and the extract was shown to cause the inhibition of ACE activity in a manner depending on its concentration. Kinetic analysis indicated that this enzyme inhibition was accompanied by an increase in the Km value without any change in Vmax. Further studies suggested that putative inhibitory substances contained in the extract might be heat stable and dialyzable, and recovered mostly in the peptide fraction obtained by a spin-column separation and a high performance liquid chromatography (HPLC) fractionation. Therefore, the extract was speculated to contain small-size peptides responsible for the inhibitory effect of okara extract on ACE activity, and could be expected to improve the hypertensive conditions by reducing the production of hypertensive peptide.